1993
DOI: 10.1002/anie.199307331
|View full text |Cite
|
Sign up to set email alerts
|

Titanium‐Catalyzed Epoxy–Hydroxylation of Allylic Alcohols: A Convenient Diastereoselective Synthesis of Epoxy Diols

Abstract: In a two‐step one‐pot procedure the allylic alcohol 1 can be converted diastereoselectively into the epoxy diols (S*,R*,S*)‐ and (S*,R*,R*)‐3 (d.r.  95: 5), simply by adding a catalytic amount of Ti(OiPr)4, to a photooxygenated solution of the allylic alcohol 1, and stopping the reaction after the complete conversion of the hydroperoxide (S*,S*)‐2, which is present in addition to the R*,S* isomer. TTP  tetraphenylporphyrin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This intramolecular titaniumcatalyzed epoxidation was further incorporated into a one-pot two-step sequence, in which the chiral allylic alcohol is transformed into an epoxy diol with high yield and high diastereoselectivity (Scheme 51). [84] Interestingly, the authors have shown that the major S,Sdiastereoisomer reacts faster (within minutes) than the minor R,S-isomer (within hours), allowing the kinetic resolution of the diastereoisomeric mixture. Overall, the sequence ene reaction of singlet oxygen/Ti-catalyzed epoxidation allows the construction of four adjacent chiral centers with high regio-and diastereo-control from a relatively simple chiral allylic alcohol.…”
Section: β-Hydroxy Hydroperoxides As Epoxidation Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This intramolecular titaniumcatalyzed epoxidation was further incorporated into a one-pot two-step sequence, in which the chiral allylic alcohol is transformed into an epoxy diol with high yield and high diastereoselectivity (Scheme 51). [84] Interestingly, the authors have shown that the major S,Sdiastereoisomer reacts faster (within minutes) than the minor R,S-isomer (within hours), allowing the kinetic resolution of the diastereoisomeric mixture. Overall, the sequence ene reaction of singlet oxygen/Ti-catalyzed epoxidation allows the construction of four adjacent chiral centers with high regio-and diastereo-control from a relatively simple chiral allylic alcohol.…”
Section: β-Hydroxy Hydroperoxides As Epoxidation Agentsmentioning
confidence: 99%
“…This intramolecular titanium‐catalyzed epoxidation was further incorporated into a one‐pot two‐step sequence, in which the chiral allylic alcohol is transformed into an epoxy diol with high yield and high diastereoselectivity (Scheme 51). [84] …”
Section: Applications Of β‐Hydroxy Hydroperoxidesmentioning
confidence: 99%
“…OOH This type of chemistry has been extended to the preparation of epoxy diols from chiral allylic alcohols (eq 16). 13, 14 The methodology is impressive in that three successive chiral centers are constructed with predictable configuration. Furthermore, the rapid rate of the isomerization process is remarkable, given that α,βunsaturated diols are generally poor substrates for titanium metalmediated epoxidations.…”
Section: Ohmentioning
confidence: 99%